Providing Lactation Education in the Post-Partum Period on the Success of Exclusive Breastfeeding : Sistematik Literature Review - Hamdiyah; Ediyono, Suryo (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2026)
Introduction: Exclusive breastfeeding during the postpartum period is crucial for optimal infant health and growth, but its success rate remains low. Lactation education for postpartum mothers is an effective intervention in improving mothers' knowledge, skills, and attitudes towards exclusive breastfeeding. This systematic literature review analyzed various studies that discussed the effect of lactation education on the success of exclusive breastfeeding. The literature search strategy was conducted using the PubMed and Schoolar databases. Inclusion criteria included: a) articles from 2020–2025, b) intervention studies (RCTs, quasi-experiments, mixed methods), c) pregnant women, postpartum mothers, and d) publications in English or Indonesian. The review results showed that lactation education in the form of counseling, breastfeeding technique training, and the use of educational media such as lactation technique videos significantly improved mothers' ability to provide exclusive breastfeeding, reduced breastfeeding problems, and increased the frequency and duration of breastfeeding. In conclusion, lactation education is an important strategy that can empower postpartum mothers to successfully provide exclusive breastfeeding, and is recommended for routine and continuous implementation by health workers. A literature search was conducted through PubMed and Elicit databases, with inclusion criteria for intervention studies covering the 2020–2025 period. Conclution indicate that culturally based interventions, such as health education through local wisdom, strengthening family food security, empowering mothers, and postpartum psychosocial support, have been shown to be effective in improving breastfeeding practices, feeding behaviors, and mother-child bonding. In conclusion, adaptive culturally based interventions have significant potential to support stunting prevention